(untitled) (The Pakistan Development Review, 1986)
The purpose of this paper is to analyse, compare and explain income inequalities in the four provinces of Pakistan on the basis of decomposition analysis. Overall income inequality is decomposed into various categories of inequalities in such a manner that the relative importance of each category can be quantified. Decomposition analysis searches for the main origins of income inequality not only within or between provinces, but also within and between urban and rural areas, labour income and non-labour income, etc. Identification of origins of inequality is important if policies aiming at reducing inequalities are considered. Clearly, different causes require different policies. A large ’decomposition tree’ built for Pakistan recently [2] which provides information on the components of inequality is presented in the accompanying chart. The structure of inequalities in the four provinces is analysed on the basis of this ’decomposition tree’.